Amphotericin B tissue penetration and pharmacokinetics in healthy and Candida albicans-infected rats: insights from microdialysis and population modeling - Santos, Valdeene Vieira; Pereira, Laiz Campos; de Araújo, Jackeline Marley Santos; Borges, Matheus Antônio da Hora; Brandão, Carolina Magalhães; Santos, Luisa Oliveira; Villarreal, Cristiane Flora; Azeredo, Francine Johansson (Frontiers in Pharmacology, 2025)
IntroductionThis study evaluated the relationship between total plasma and free kidney concentrations of amphotericin B (AmB) in healthy and C. albicans-infected Wistar rats using microdialysis and has the potential to significantly impact future research in this field and promote the development of antifungal drugs. The findings of this study, which show that plasma levels are a good predictor for AmB kidney concentrations and can be used to optimize its dosing regimen, underscore the importance of this research.MethodsMicrodialysis probe recovery rates were determined by dialysis and retrodialysis in vitro, as well as by retrodialysis in vivo. The intravenous (i.v.) administration of 2.5 × 106 CFU/mL of C. albicans ATCC induced the infection. A 2.5 mg/kg i.v. bolus was used in healthy and C. albicans-infected rats (n = 6/group). Plasma and microdialysate samples were analyzed using HPLC-diode-array detection. AmB tissue penetration was analyzed using the ratio between the total plasma and kidney concentrations and population pharmacokinetics (PopPK) to assess the impact of the infection on the pharmacokinetic parameters. The chosen flow rate was set to 1.5 μL/min, and there was no statistical difference between the relative recovery values when changing AmB concentrations.Results and DiscussionThe in vivo relative recovery was determined to be 10.9% ± 3.7%. The antifungal tissue penetration was 0.77 and 0.71 for the healthy and infected animals, respectively. The structural PK model with two compartments and linear elimination describes the concentration versus time profile of AmB simultaneously in the plasma and tissue. Infection by C. albicans does not interfere with AmB kidney penetration. AmB protein binding is demonstrated to be nonlinear and dependent on the AmB concentration in the plasma of healthy and infected animals.